2021
DOI: 10.1182/bloodadvances.2021004304
|View full text |Cite
|
Sign up to set email alerts
|

HGAL inhibits lymphoma dissemination by interacting with multiple cytoskeletal proteins

Abstract: Human Germinal Center Associated Lymphoma (HGAL) is an adaptor protein specifically expressed in germinal center lymphocytes. High expression of HGAL is a predictor of prolonged survival of Diffuse Large B-Cell (DLBCL) and classical Hodgkin lymphomas. Furthermore, HGAL expression is associated with early stage DLBCL, thus potentially limiting lymphoma dissemination. In our previous studies, we demonstrated that HGAL regulates B-cell receptor signaling and cell motility in vitro and deciphered some molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 44 publications
2
7
0
10
Order By: Relevance
“…This leads to the prolongation of the myosin-actin interaction, contributing to a decreased ability of myosin to translocate actin. An HGAL-induced decrease in actin filament sliding velocity, as demonstrated by the in vitro motility assays, supports this idea [104]. Alternatively, but not mutually exclusive, HGAL binding to myosin and/or actin may serve as a 'load' that resists actin filament motion, hence leading to the same effects [104].…”
Section: Hgal Directly Interacts With Myosin and Actin Increasing The...mentioning
confidence: 85%
See 4 more Smart Citations
“…This leads to the prolongation of the myosin-actin interaction, contributing to a decreased ability of myosin to translocate actin. An HGAL-induced decrease in actin filament sliding velocity, as demonstrated by the in vitro motility assays, supports this idea [104]. Alternatively, but not mutually exclusive, HGAL binding to myosin and/or actin may serve as a 'load' that resists actin filament motion, hence leading to the same effects [104].…”
Section: Hgal Directly Interacts With Myosin and Actin Increasing The...mentioning
confidence: 85%
“…The mechanisms regulating the motility of GC lymphocytes and lymphoma cells are only partially elucidated [98][99][100][101][102]. It was demonstrated that HGAL, in addition to regulating BCR signaling [55,57,58], also decreases spontaneous and stimuli induced [e.g., stromal cell derived factor 1 (SDF-1), IL-6, fibronectin] motility by several molecular mechanisms [56,[103][104][105].…”
Section: Hgal Regulates Cell Motilitymentioning
confidence: 99%
See 3 more Smart Citations